SOAR as a Mediator of the Relationship Between Emotional Intelligence and Collaboration Among Professionals Working in Teams: Implications for Entrepreneurial Teams - Matthew L. Cole (SAGE Open, 2018)
A majority of ventures are started by entrepreneurial teams rather than individuals. More than half of team-based new venture failures are believed to be due to problems with the entrepreneurial team. Collaboration among entrepreneurial team members is important for increasing the likelihood of successful venture outcomes. We investigated collaboration in professionals working in teams using survey methodology. Results found a framework for collaborative dialogue, SOAR (strengths, opportunities, aspirations, and results), mediates the relationship between emotional intelligence and team collaboration. We discuss practical recommendations to increase the strength of the relationship between emotional intelligence and collaboration to increase entrepreneurial team performance. For example, behavioral coaches are recommended to use dialogical exercises to help team members develop emotional intelligence competencies of awareness and regulation of emtions in self and others. Entrepreneurs are recommended to create teams that build on member strengths and aspirations, and identify opportunities for achieving measurable positive results.